Increasing microplastic concentrations have nonlinear impacts on the physiology of reef-building corals - Tirpitz, Vanessa; Hutter, Mona; Hutter, Hanna; Prume, Julia; Koch, Martin; Wilke, Thomas; Reichert, Jessica; Justus Liebig University Giessen (My University, 2025)
The pollution of marine environments with plastics, particularly microplastic (MP, i.e., plastic particles <5 mm), is a major threat to marine biota, including corals. While the effects of MPs are increasingly well understood, knowledge of how different concentrations of naturally occurring MP mixtures affect reef-building corals is still limited. Therefore, we aimed to elucidate the relationship of MP concentrations and their effects on reef-building corals. For this, we exposed two reef-building coral species (Stylophora pistillata and Pocillopora verrucosa) in a 12-week experiment to MPs at a gradient of concentrations (0, 0.1, 1, 10, and 100 mg⋅L􀀀 1). Specifically, we examined effects on the coral host physiology (i.e., surface and volume growth, calcification, necrosis, and polyp activity), and the photosynthetic activity of the photosymbionts (i.e., effective and maximum quantum yield, maximum relative electron transport rate, minimum saturating irradiance, and light capture efficiency). To mimic natural conditions, we used a MP mixture consisting of six polymers in forms of fibers and fragments. Both coral species showed reduced growth rates, necrosis, lower polyp activity, and an upregulation of photosynthesis, which intensified with increasing MP concentrations. While the effects on the coral host mostly showed basic linear or nonlinear dose-response relationships, the effects on the photosymbionts revealed more complex nonlinear dose-response relationships, and photosynthesis was only upregulated after a species-specific threshold. We found that high and extreme pollution scenarios caused strong adverse effects on coral physiology, while current low to moderate concentrations had minor effects. Increasing concentrations had amplifying effects, likely due to the disproportionately higher frequency of entanglement, leading to more frequent direct contact and potential transfer of toxins or pathogens. These results suggest that corals can cope with current average pollution levels. However, they also highlight the need for measures to limit permanent increases of MP pollution to protect the health of coral reefs.
Keywords: ddc:570